Knowledge of Postpartum Mothers About Umbilical Cord Care in Newborns - Fauzia, Eva (Indonesian Health Journal (IHJ), 2023)
cord is a unique network consisting of two arteries and one vein protected by sheathed mucoid connective tissue by a thin mucous membrane. During pregnancy, the placenta provides all the nutrients for the growing fetus and excretes waste products through the umbilical cord. This research uses a descriptive research method, using secondary data in the form of total data on pregnant mothers taken from the monthly report at the health center Mount Sari _ from February to March 2023. Each respondent has different knowledge; some respondents know and understand how to prevent or treat infection and apply it in everyday life so that respondents can answer questions properly. Meanwhile, some respondents needed help understanding how to prevent or treat infection and had not applied it in their daily lives, making it difficult to answer questions from researchers